AGROINDUSTRIAL WASTE AND SEWAGE SLUDGE AS SUBSTRATE FOR THE Eucalyptus urograndis SEEDLING PRODUCTIONS - Melo Silva, Francisca Alcivania de [UNESP]; Nunes, Giovanna Margheri; Zanon, Jair Augusto; Guerrine, Irae Amaral [UNESP]; Silva, Reginaldo Barboza da [UNESP] (Centro Pesquisas Florestais, Ufsm, 2018)
The objectives of this study were to evaluate the use of substrates based on residues from the peach palm and composted sewage sludge in the production of Eucalyptus urograndis seedlings with different levels of fertilizer and to compare them to a commercial substrate. Three substrates based on sewage sludge and peach palm were used in proportions: 50/50; 33/66 and 25/75 v: v, four levels of granular fertilizer (0, 2.0, 4.0 and 6.0 g dm())(-3) and a commercial substrate. The diameter of the colon, height of the plants, H/D, dry matter of shoot and root and quality of the log were evaluated. The sewage sludge use and peach palm has viability as a substrate in the production of Eucalyptus urograndis seedlings, with equal or superior performance to the commercial substrate. The level increase of the granulated fertilizer provided significant effects on the quality of the seedlings, being recommended the use of above 4.0 g dm(-3).
Keywords: biosolids; nurseries; substrate; eucalyptus